CORNUAL ECTOPIC PREGNANCIES IN RECURRENT ECTOPIC PREGNANCIES AFTER SALPINECTOMY: CASE REPORTS - Dhaniel Theolia Persadanta Ginting; Patricia Riwiris Sry Rezeki Samosir; Kevin Nicholas Rumahorbo; Binarwan Halim (Journal of Public Health Science, 2026)
Ectopic pregnancy remains a major cause of maternal morbidity and mortality in early pregnancy. Recurrent ectopic pregnancy represents a significant clinical challenge, particularly in women with a previous history of ectopic pregnancy and tubal surgery such as salpingectomy. Cornual or interstitial ectopic pregnancy is a rare form of ectopic implantation, accounting for approximately 2–4% of all ectopic pregnancies. Despite its rarity, this condition carries a higher risk of severe hemorrhage due to its location within the highly vascularized uterine cornua. Case Presentasion: A 34-year-old woman with a history of ectopic pregnancy treated with salpingectomy presented with worsening lower abdominal pain in early pregnancy. Physical examination, laboratory evaluation and ultrasonography suggested a suspected ectopic pregnancy. Emergency laparoscopy confirmed a cornual ectopic pregnancy with hematoma and pelvic adhesions. Laparoscopic cornual resection, hematoma evacuation, hystero-raphy, and adhesiolysis were performed successfully without complications. The patient recovered well and was discharged in stable condition. Discussion: Recurrent ectopic pregnancy is a known complication in patients with a prior history of ectopic pregnancy and tubal surgery. Although salpingectomy reduces the likelihood of tubal ectopic pregnancy on the affected side, implantation may still occur in other locations, including the interstitial or cornual region. Cornual ectopic pregnancy can grow longer before rupture due to the surrounding myometrial tissue, which may delay diagnosis but increases the risk of catastrophic bleeding once rupture occurs. Laparoscopic management is preferred in hemodynamically stable patients because it offers less surgical trauma, shorter hospital stay, and faster recovery. Conclusion: Cornual ectopic pregnancy may occur as a recurrent ectopic pregnancy even after salpingectomy. Early recognition and prompt surgical intervention are essential to prevent life-threatening complications. Laparoscopic management provides an effective and minimally invasive treatment option with favorable clinical outcomes.